Upaya Peningkatan Produktivitas dengan Menggunakan Pendekatan DMAIC pada PT X - Kariza Verena Chandra; Prayonne Adi (Jurnal Titra, 2022)
PT X is a global No. 1 in the world. To remain the best, companies need to maintain and increase productivity. This is because productivity is a measure of the success of a process. The purpose of this study is to find out the causes of low productivity and make efforts to reduce the gap between planning and actual. The approach used in this research is DMAIC. It was found that the factors causing the productivity target not to be achieved were due to the gap in working time/machines running and the number of workers who did not match the plan with the actual. This gap is caused by the efficiency of the production process which is still not on target. This causes the output of the production process is not as planned. This impact resulted in the amount of time and labor needed to be not in accordance with what was planned to achieve the desired productivity. The suggestions for improvement are the visual control display design, plan of action, and control plan sheet. This proposal is considered to be able to assist planning and production to control the productivity of the production process.